Evaluation of maternal preferences for neonatal male circumcision in Enugu Nigeria - Uchechukwu Obiora Ezomike; Josephat Maduabuchi Chinawa; Joseph T Enebe; Euzebus Chinonye Ezugwu; Elias C Aniwada; Nkeiruka Elsie Ezomike; Awoere T Chinawa; Sebastian Okwuchukwu Ekenze (Wolters Kluwer Medknow Publications, 2022)
Background: Although circumcision in male neonates is one of the most common procedures performed in neonatal surgery, mothers' preferences concerning the aspects of circumcision are not well-known. Since mother is the likely parent to present child for circumcision, her preferences should be given adequate consideration. Objectives: The objective of this study is to evaluate maternal preferences for neonatal male circumcision in Enugu. Methodology: A cross-sectional study where questionnaire was distributed by the researchers to consenting pregnant women attending antenatal clinics in two teaching hospitals in Enugu. Data analysis was performed using the SPSS. The results presented as means, percentages and tables. Test for significance was done using the Chi-square test. Results: Four hundred and sixty-one pregnant women participated in the study. Ninety-five percent (438/461) wanted circumcision and 83.5% (385/461) wanted it on or before the 8th day of life. The reasons were cultural/religious in 69% (302/447). Fifty-four percent (250/461) had no preferences as to methods, but for those who had, Plastibell was most preferred method in 28% (129/461) while 76% (235/309) preferred circumcision to be done in hospital. In 49.2% (227/461) preferred personnel were nurses but 79.6% (367/461) wanted doctors to attend to post-circumcision complications. In 79.2% (365/461), mothers will not insist on the use of anaesthesia for circumcision. Mothers with circumcised husbands were significantly more willing to circumcise a male child (P = 0.0018). Higher educational status of mother was significantly related to willingness to insist on the use of anaesthesia (P = 0.046) and use of analgesics after circumcision (P = 0.001). Conclusions: Most mothers prefer neonatal male circumcision by nurses, while preferring doctors for post-circumcision complications. These choices are not affected by parents' educational status. Mothers with circumcised husbands accepted circumcision more than those with uncircumcised husbands. Higher maternal education encourages anaesthesia during circumcision and post-circumcision analgesia.